Anticancer Activity of a Broccoli Derivative, Sulforaphane, in Barrett Adenocarcinoma: Potential Use in Chemoprevention and as Adjuvant in Chemotherapy - Qazi, Aamer (Neoplasia Press Inc., 2010)
INTRODUCTION: The incidence of Barrett esophageal adenocarcinoma (BEAC) has been increasing at an alarming rate in western countries. In this study, we have evaluated the therapeutic potential of sulforaphane (SFN), an antioxidant derived from broccoli, in BEAC. METHODS: BEAC cells were treated with SFN, alone or in combination with chemotherapeutic, paclitaxel, or telomerase-inhibiting agents (MST-312, GRN163L), and live cell number determined at various time points. The effect on drug resistance/chemosensitivity was evaluated by rhodamine efflux assay. Apoptosis was detected by annexin V labeling and Western blot analysis of poly(ADP-ribose) polymerase cleavage. Effects on genes implicated in cell cycle and apoptosis were determined by Western blot analyses. To evaluate the efficacy in vivo, BEAC cells were injected subcutaneously in severe combined immunodeficient mice, and after the appearance of palpable tumors, mice were treated with SFN. RESULTS: SFN induced both time- and dose-dependent decline in cell survival, cell cycle arrest, and apoptosis. The treatment with SFN also suppressed the expression of multidrug resistance protein, reduced drug efflux, and increased anticancer activity of other antiproliferative agents including paclitaxel. A significant reduction in tumor volume was also observed by SFN in a subcutaneous tumor model of BEAC. Anticancer activity could be attributed to the induction of caspase 8 and p21 and down-regulation of hsp90, a molecular chaperon required for activity of several proliferation-associated proteins. CONCLUSIONS: These data indicate that a natural product with antioxidant properties from broccoli has great potential to be used in chemoprevention and treatment of BEAC.